The tumor necrosis factor-inducible zinc finger protein A20 interacts with TRAF1/TRAF2 and inhibits NF-kappaB activation. - Song, H Y (1996)
TRAF1 and TRAF2 form an oligomeric complex that associates with the cytoplasmic domains of various members of the tumor necrosis factor (TNF) receptor superfamily. TRAF2 action is required for activation of the transcription factor NF-kappaB triggered by TNF and the CD40 ligand. Here we show that TRAF1 and TRAF2 interact with A20, a zinc finger protein, whose expression is induced by agents that activate NF-kappaB. Mutational analysis revealed that the N-terminal half of A20 interacts with the conserved C-terminal TRAF domain of TRAF1 and TRAF2. In cotransfection experiments, A20 blocked TRAF2-mediated NF-kappaB activation. A20 also inhibited TNF and IL-1-induced NF-kappaB activation, suggesting that it may inhibit NF-kappaB activation signaled by diverse stimuli. The ability of A20 to block NF-kappaB activation was mapped to its C-terminal zinc finger domain. Thus, A20 is composed of two functionally distinct domains, an N-terminal TRAF binding domain that recruits A20 to the TRAF2-TRAF1 complex and a C-terminal domain that mediates inhibition of NF-kappaB activation. Our findings suggest a possible molecular mechanism that could explain A20's ability to negatively regulate its own TNF-inducible expression.